2011
DOI: 10.2337/dc10-2121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurse Case Management Compared With Usual Care on Controlling Cardiovascular Risk Factors in Patients With Diabetes

Abstract: OBJECTIVETo determine whether nurse case management with a therapeutic algorithm could effectively improve rates of control for hypertension, hyperglycemia, and hyperlipidemia compared with usual care among veterans with diabetes.RESEARCH DESIGN AND METHODSA randomized controlled trial of diabetic patients that had blood pressure (BP) >140/90 mmHg, hemoglobin A1c (HbA1c) >9.0%, or LDL >100 mg/dL. Intervention patients received case management (n = 278) versus usual care (n = 278) over a 1-year period. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…Twenty-eight interventions 2123,2528,34,36,38,40,41,4345,49,50,52,56,57,64,65,7275,95,97 included nurses, 15 interventions 2932,37,39,42,47,51,54,55,61,68,71,76 included pharmacists, and five interventions 33,53,62,63,96 included both nurses and pharmacists. Detailed evidence tables are available at www.thecommunityguide.org/cvd/SETteambasedcare.pdf.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight interventions 2123,2528,34,36,38,40,41,4345,49,50,52,56,57,64,65,7275,95,97 included nurses, 15 interventions 2932,37,39,42,47,51,54,55,61,68,71,76 included pharmacists, and five interventions 33,53,62,63,96 included both nurses and pharmacists. Detailed evidence tables are available at www.thecommunityguide.org/cvd/SETteambasedcare.pdf.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The median effect estimate from studies within the Veterans Affairs (VA) system 25,27,33,43,47,51,74,96 was 5.9 pct pts; an investigator involved in two VA studies 25,27 postulated (H. Bosworth, Duke University School of Medicine, personal communication, 2012) that this lower number is likely due to elements of team-based care already instituted in usual care processes at the VA and high baseline levels of patients with controlled BP. Median reductions in SBP and DBP from these studies were similar to overall estimates (Table 3).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Diabetic patients who were monitored by a nurse case manager, under the direction of a family physician, or an endocrinologist, had improved glycemic control within 12 months [4] and improved blood pressure, cholesterol and glycemic control at one year [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In order to bridge the cultural divide between minority groups such as Māori and New Zealand's Pākehā dominated western medicine and better manage chronic conditions such as CVD, culturally appropriate nurses should be employed by DHB's and attached to PHO's as chronic care managers. The role of a care manager is to develop individualised care plans in collaboration with the patient and the care providers that optimize the patient's health status and quality of life [73][74][75][76]. A number of studies have demonstrated the effectiveness of such patient-provider collaborations, including the LEONARDO project, with its extension the NARDINO project and the studies of highlighted the necessity to standardise the role chronic care managers within primary care to improve the implementation of chronic disease management strategies [69,73].…”
Section: Moving Forwardmentioning
confidence: 99%